STUDI PARAMETER FISIKA DAN KIMIA DAERAH PENANGKAPAN IKAN PERAIRAN SELAT ASAM KABUPATEN KEPULAUAN MERANTI PROPINSI RIAU - Sari, T. Ersti Yulika; ', Usman (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
Survey and measurement of aquatic environmental condition of SelatAsamwater was conducted in order to know the physical, chemical and biologicalparameter of SelatAsam water. Measurement was conducted at ten stations a longthe SelatAsam, and the data was collected has been analysis by using descriptiveanalysis. Nitrate and phosphate was analyzed in the laboratory of Ecology in theFisheries and Marine Science Faculty University of Riau.The result of this observation for a environment parameter were as followingtemperatures 30,10C - 31,80C, current speed 0,34 m/s - 0,77 m/s, brightness 0,40 m -1,65 m, depth 2,0 m - 23,5 m, salinity 21‰- 31‰, dissolved oxygen 7,29 mg/l -10,83 mg/l, pH 7 – 8, nitratconsentration 0,02 ppm - 0,24 ppm andphosphatconsentration 0,02 ppm - 0,51 ppm.Type of fish cought by these fishinggears were (Acetessp), (Metapenaeussp), (Parapaenopsissp), (Alphasessp),(Trissasp), (Steloporussp), (Setipinnasp), (Harpodonsp), (Trichiurus sp), (Loligo sp),(Cybium sp), (Maraenesox sp) and (Polynemus sp).According to the result analysis, can be concluded that the aquatic environmentin the coastal area of SelatAsam was still suffientas habitat for living organisms andmay be used for fishing activities